Coronary risk factors in Acute Coronary Syndrome Patients in Yemen - Al-Huthi, Mohammed Ali; Jayed , Dhaifullah; Aldolaee, Mohammed (Thamar University Journal of Natural & Applied Sciences, 2023)
Background: A comparative retrospective study has made to compare the distribution of risk factors and complications in acute coronary syndrome (ACS) patients and other cardiac patients.Methods: Records of 768 patients from Sana’a city and other cardiac patients in Yemen. To assess the risk factors for acute coronary syndrome (ACS); age, hypertension, diabetes mellitus, hyperlipidemia, cigarette smoking and reported history and family history of coronary artery disease (CAD). To assess the complications such as heart failure, arrhythmias and cerebro-vascular accident (CVA).Results: The mean age of acute coronary syndrome patients was significantly lower than other cardiac disease patients 56.8 year vs. 55.3 years; p= 0.007. History of hyperlipidemia was significantly higher acute coronary syndrome patients than other cardiac patients 49.2% vs. 38.3%; p=0.002. Reported history of coronary artery disease was also significantly higher among ACS patients. Hypertension, history of diabetes mellitus, cigarette smoking and reported family history of coronary artery disease were comparable among acute coronary syndrome patients and other cardiac patients. In-hospital complications: Cerebro-vascular accident was significantly higher among ACS patients than other cardiac patients 7.8 % vs. 4.4 %; p= 0.0001. Heart failure and arrhythmias rates were comparable. Wall motion abnormalities were comparable 79.2 vs. 73.2; p=0.51. While Ejection Fraction was lower in ACS patients than other cardiac patients 49.8.8% vs. 54.8; p=0.0001.Conclusions: The mean age was higher among acute coronary syndrome patients. History of hyperlipidemia and history of coronary artery disease were higher among acute coronary syndrome patients. Cerebro-vascular accident rate was higher in acute coronary syndrome patients.